2012
DOI: 10.1002/jbio.201200078
|View full text |Cite
|
Sign up to set email alerts
|

Laser‐driven beam lines for delivering intensity modulated radiation therapy with particle beams

Abstract: Laser-accelerated particles are a promising option for radiation therapy of cancer by potentially combining a compact, cost-efficient treatment unit with the physical advantages of charged particle beams. To design such a treatment unit we consider different dose delivery schemes and analyze the necessary devices in the required particle beam line for each case. Furthermore, we point out that laser-driven treatment units may be ideal tools for motion adaptation during radiotherapy. Reasons for this are the pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…In recent years, short‐pulse high‐power lasers have shown their ability to drive particle beams for cells and tissue radiation. The results obtained so far in studying their biological effects are encouraging: laser‐accelerated particle beams have the potential of finding use in radiotherapy . Laser‐driven ionizing radiation (gamma beams, x rays, ions, or electrons) can be generated in pulses with durations of fs to ns, depending on the time length of the driving laser pulse, with doses up to several Gy/pulse.…”
Section: High Dose‐rate Radiation Sourcesmentioning
confidence: 99%
“…In recent years, short‐pulse high‐power lasers have shown their ability to drive particle beams for cells and tissue radiation. The results obtained so far in studying their biological effects are encouraging: laser‐accelerated particle beams have the potential of finding use in radiotherapy . Laser‐driven ionizing radiation (gamma beams, x rays, ions, or electrons) can be generated in pulses with durations of fs to ns, depending on the time length of the driving laser pulse, with doses up to several Gy/pulse.…”
Section: High Dose‐rate Radiation Sourcesmentioning
confidence: 99%
“…One of the advertised benefits of protons from a laser source is that an all-optical gantry, using mirrors instead of bending magnets, can provide a substantially more compact and inexpensive means of isocentric beam delivery [2,3,5]. As mentioned above, though, the plume of particles from the target must be carefully tailored to meet the requirements of the treatment, i.e., the equivalent of today's gantry nozzle must be provided for.…”
Section: Isocentric Gantrymentioning
confidence: 99%
“…Proton energies and intensities are still not close to the levels suitable for therapy applications, even with the most powerful lasers. The bold predictions for rapid advances towards clinically viable laser-based proton accelerator systems [2][3][4][5][6] have proven premature. Meanwhile, proton therapy facilities based on conventional accelerators continue to expand, with great strides being made in size and cost reduction [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Instead of transferring all 2211 spectra to the optimizer, a preselection of spectra is performed. To use as many protons as possible from the initial spectrum, the dose will be delivered via the axial clustering dose delivery method described by Schell and Wilkens 24 and Hofmann et al 18 Therefore, as in the common spot scanning technique, spots are placed within the target along pencil beams for every field. These spots are arranged on a user defined grid covering the whole target volume and would be treated with single Bragg peaks in conventional intensity modulated proton therapy (IMPT).…”
Section: B Treatment Planning Systemmentioning
confidence: 99%
“…Consequently, a beam line is required which is able to collect a divergent proton beam with a broad energy spectrum efficiently, guide this beam to the patient, and additionally allow for patient specific dose delivery and control. Ideally, the whole beam line is able to rotate around a fixed room isocenter to provide enough degrees of freedom for the treatment as proposed by Ma et al 17 or by Hofmann et al 18 To enable a patient specific delivery, the beam line must offer an energy selection system (ESS) to choose desired parts from the initial proton spectrum. One way to realize such an ESS can be accomplished by a chicane consisting of four dipole magnets as proposed by Fourkal et al 19 and Yogo et al 20 However, Faby and Wilkens 21 have shown that such a setup is not the optimal solution for an exponentially decaying, broad proton spectrum with respect to shielding of secondary radiation.…”
Section: Introductionmentioning
confidence: 99%